Utilizing Heart Rate Variability for Coaching Athletes During and After Viral Infection: A Case Report in an Elite Endurance Athlete - Laura Hottenrott; Thomas Gronwald; Kuno Hottenrott; Thimo Wiewelhove; Alexander Ferrauti (Frontiers Media S.A., 2021)
Background: Viral diseases have different individual progressions and can lead to considerable risks/long-term consequences. Therefore, it is not suitable to give general recommendations on a time off from training for athletes. This case report aims to investigate the relevance of detecting heart rate (HR) and HR variability (HRV) during an orthostatic test (OT) to monitor the progression and recovery process during and after a viral disease in an elite endurance athlete.Methods: A 30-year-old elite marathon runner contracted a viral infection (upper respiratory tract infection) 4 weeks after a marathon race. RR intervals in HR time series in supine and standing positions were monitored daily in the morning. Analyzed parameters included HR, the time-domain HRV parameter root mean square of successive difference (RMSSD), peak HR (HRpeak) in a standing position, and the time to HR peak (tHRpeak).Results: During the 6-day viral infection period, HR increased significantly by an average of 11 bpm in the supine position and by 22 bpm in the standing position. In addition, the RMSSD decreased from 20.8 to 4.2 ms, the HRpeak decreased by 13 bpm, and the tHRpeak increased by 18 s in the standing position significantly. There were no significant changes in the pre-viral infection RMSSD values in the supine position. The viral infection led to a significant change in HR and HRV parameters. The cardiac autonomic system reacted more sensitively in the standing position compared to the supine position after a viral infection in the present case study.Conclusion: These data have provided supportive rationale as to why the OT with a change from supine to standing body position and the detection of different indicators based on HR and a vagal driven time-domain HRV parameter (RMSSD) is likely to be useful to detect viral diseases early on when implemented in daily routine. Given the case study nature of the findings, future research has to be conducted to investigate whether the use of the OT might be able to offer an innovative, non-invasive, and time-efficient possibility to detect and evaluate the health status of (elite endurance) athletes.